Integrated eco-design decision making for sustainable product design - Awanis, Romli (2015)
'Design for Sustainability' has evolved since the 1990s; its focus is on sustainable product development by integrating the three main components of people, profit, and planet. These components have become fundamental to product innovation. Design for sustainability aims at making green products; it addresses the best way to meet consumers' needs in a sustainable way. In order to produce a more sustainable product, the implementation of sustainability considerations should be applied at the earliest possible stage of product design.